Workshop : Gamification Untuk Penguatan Karakter Peserta Didik Sekolah Dasar di Kota Metro - Ismu Sukamto; Ujang Efendi; Fadhilah Khairani; Hervin Maulina; Jody Setya Hermawan (Jurusan Ilmu Pendidikan - Universitas Lampung, 2022)
Characteristics of elementary school students (SD) are more dominant in psychomotor activity. Classroom learning should accommodate this so that student motivation is maintained during the learning process. Motivation is important considering that mastery of knowledge will be more optimal if students enjoy the learning process. Traditional learning is still found in Way Kanan Regency, so it is necessary to learn that accommodates these characteristics. One way that is considered appropriate is the application of the concept of gamification. The purpose of this service is to provide counseling and learning training with the concept of gamification to elementary school educators, develop the potential of students who are not yet optimal due to traditional learning, and foster the spirit of professionalism of elementary school educators. This service uses counseling and training methods and involves 25 educators in Way Kanan Regency. The instruments used are tests and portfolios as measuring tools to evaluate and sustain service. This service is expected to be a reference for innovative and productive learning to improve the character of students as a provision to face the challenges of the digital era.